ANALISIS PENGGUNAAN RASIO KEUANGAN DALAM MENDETEKSI KECURANGAN PELAPORAN KEUANGAN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2018) - Widhayanti, Marlita Dwi; Utomo, Dwi Cahyo (Diponegoro Journal of Accounting, 2020)
This research aims to analyze financial ratios (leverage ratios, profitability ratios, asset composition ratios, liquidity ratios, and capital turnover ratios) in detecting fraudulent financial reporting. The dependent variable in this research is fraudulent financial reporting measured by Beneish M-Score to identify companies that are fraud and nonfraud.. The independent variables in this research are leverage ratio, profitability ratio, asset composition ratio, liquidity ratio, and capital turnover ratio. This research uses quantitative methods by using logistic regression analysis in SPSS 23 software. The population of this research is manufacturing companies listed in the Indonesia Stock Exchange in 2014 - 2018. The samples are selected using a purposive sampling method and acquired  440 firms. The results of the test show that the profitability ratios and asset composition ratios have the effect of detecting fraudulent financial reporting. Meanwhile, leverage ratios, liquidity ratios, and capital turnover ratios have no effect in detecting fraudulent financial reporting.